2020
DOI: 10.1101/2020.06.10.20127720
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-based differences in clearance of chronicPlasmodium falciparuminfection

Abstract: Background: Multiple studies have reported a higher prevalence of malaria infection in males compared to females. However, it remains unknown whether this is due to differences in behavioral factors or biological sex playing a direct role in the host response to the malaria parasite. Methods and Findings: To test the hypothesis that sex-based differences in host-parasite interactions affect the epidemiology of malaria, we intensively followed a cohort of individuals living in a malaria endemic area of easter… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 40 publications
1
18
1
Order By: Relevance
“…Moreover, hormonal differences might play the role in such a way that testosterone was associated with decreased adaptive immunity against malaria [53]. Briggs and the colleagues have also thought that females cleared their infections at a faster rate than males [54] which might support the lower prevalence of malaria among females in the current study.…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, hormonal differences might play the role in such a way that testosterone was associated with decreased adaptive immunity against malaria [53]. Briggs and the colleagues have also thought that females cleared their infections at a faster rate than males [54] which might support the lower prevalence of malaria among females in the current study.…”
Section: Discussionsupporting
confidence: 52%
“…For each experiment, between 60-80 Anopheles gambiae ss mosquitoes were offered heparinised venous blood (Vacutainer Lithium Heparin Tube 4 mL; BD Biosciences, Plymouth, UK) via two glass feeders filled with 0•5 mL of blood each. 18 10 days after feeding, mosquitoes were dissected in 0•5% mercurochrome using a stereo microscope, and examined for the presence of oocysts on the mosquito midgut under an optic microscope by two microscopists (JO and AM); P falciparum DNA (18S) was detected in infected guts by nested PCR. To assess parasite diversity over the entire follow-up period, DNA from study participants and infected mosquito midguts was analysed by amplicon deep sequencing of the apical membrane antigen 1 (AMA-1) gene, as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…A cohort study that followed individuals in a malaria endemic region has suggested that females clear asymptomatic malaria infections faster than males, and this could have an impact on approaches to eliminate the disease. 1…”
Section: Human Study Reveals Sex-based Differences In Malaria Infectionmentioning
confidence: 99%
“…A better understanding of host–parasite interactions, and how sex influences them, particularly in terms of the immune responses that result in asymptomatic infection, could help to optimise malaria eradication measures. Briggs et al 1 studied a population of 477 individuals (233 males and 244 females), living in malaria endemic regions. To detect the onset of new infections and track infections over time, frequent sampling was combined with molecular techniques (ultrasensitive quantitative PCR (qPCR) and amplicon deep-sequencing) to genotype parasite clones.…”
Section: Human Study Reveals Sex-based Differences In Malaria Infectionmentioning
confidence: 99%